2021
DOI: 10.1101/2021.01.16.21249950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Six-month Neurological and Psychiatric Outcomes in 236,379 Survivors of COVID-19

Abstract: BackgroundNeurological and psychiatric sequelae of COVID-19 have been reported, but there are limited data on incidence rates and relative risks.MethodsUsing retrospective cohort studies and time-to-event analysis, we estimated the incidence of ICD-10 diagnoses in the 6 months after a confirmed diagnosis of COVID-19: intracranial haemorrhage; ischaemic stroke; Parkinsonism; Guillain-Barré syndrome; nerve/nerve root/plexus disorders; myoneural/muscle disease; encephalitis; dementia; mood, anxiety, and psychotic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
0
32
1
10
Order By: Relevance
“…51 This was followed recently by another TriNetX analysis, this time of 236,379 patientsincluding 190,077 patients who were not hospitalized and 8,945 patients who needed critical carewhich is the largest dataset to date. 52 This study was limited by its retrospective design and reliance on electronic medical record codes. However, the study had a large sample size, and included both hospitalized and non-hospitalized patients.…”
Section: Figure1b)mentioning
confidence: 99%
See 1 more Smart Citation
“…51 This was followed recently by another TriNetX analysis, this time of 236,379 patientsincluding 190,077 patients who were not hospitalized and 8,945 patients who needed critical carewhich is the largest dataset to date. 52 This study was limited by its retrospective design and reliance on electronic medical record codes. However, the study had a large sample size, and included both hospitalized and non-hospitalized patients.…”
Section: Figure1b)mentioning
confidence: 99%
“…127 Similar findings were reported in a recent large analysis of the TriNetX platform, with an estimated 6month incidence of GBS of 0.08% in patients with COVID-19, with a hazard ratio of 2.06 (95%CI 1.43-2.96) versus patients with other respiratory tract infections. 52 Two retrospective cohort studies on the frequency of GBS met our inclusion criteria for pooled analysis. These studies had a moderate risk of bias on most domains (Supplementary Figure 2D).…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“…In the study by Taquet et al (2021) out of 236, 370 patients at 6 months, the global incidence of neurological and psychiatric pathologies was 33% of those infected with symptoms, in those who were admitted to intensive care units the incidence was 46% and in those who had encephalitis 62%. these authors showed a higher frequency of ACV, nerve, nerve root or plexus disorder, myoneural or muscle disease, dementia, mood, anxiety, or psychotic disorder.…”
Section: Patients With Long-term Neurological Sequels Of Covid-19mentioning
confidence: 97%
“…In contrast, the cases discussed by Taquet and colleagues may have presented distinct characteristics. Therefore, outcomes for this population should not be considered generalizable to all delirium patients [2]. Last, such a study design may only depict associations; attempts to classify pathways and measure causality will require more detailed study designs [2].…”
Section: Main Textmentioning
confidence: 99%
“…Alexios-Fotios A. Mentis 1,2 Background Since the COVID-19 pandemic began, there has been a steadily increasing interest on the COVID-19 infection's neurological and psychiatric sequelae, such as dementia and mood/anxiety disorders [1]. However, the majority of studies reporting on COVID-19−related neurological complications are generally confined to small series of patients and to small numbers of hospitals and are limited to locations and specialization; thus, the neuropsychiatric consequences of COVID-19 are not evaluated across a broader spectrum of population and independent geographic settings [2][3][4]. Hence, larger, more robust, and long-term data are essential to define and critically evaluate the effects of the COVID-19 pandemic on neurological and psychiatric disorders.…”
mentioning
confidence: 99%